Investigating Benefits and Drawbacks of Employee Empowerment in the Sector of Hospitality - Mehmet Ali Turkmenoglu (INTERNATIONAL RESEARCH JOURNAL OF BUSINESS STUDIES, 2019)
Employees’ empowerment has a significantly close relationship with employees’ job-related outcomes such as job satisfaction, job performance, and organizational commitment. This study aims to investigate the role of empowerment on employees’ job-related attitudes in the hospitality sector. This present study provides a literature review on concept of empowerment by explaining benefits and drawbacks of the concept. This study identifies several advantages e.g. more input of ideas, growth of interpersonal and guidance skills. The drawbacks are negative use of the power received, high risk of failures without supervision, conflicts result in less supervision among others. The study demonstrates a frame of empowerment in hospitality sector along with recommendations and implications.Keywords: Empowerment, Hospitality Sector, Job Satisfaction, Job Performance, Literature Review(1) Faculty of Economics and Administrative Sciences, Mus Alparslan University, Turkey* Corresponding Author https://doi.org/10.21632/irjbs.12.1.1-13